The embeddedness of adolescernt employment and participation in delinquency: a life course perspective - Wright, John Paul (Western criminology review, 2002)
Adolescent penetration into the labor market is a relatively new, and much understudied, phenomena. To date, limited empirical evidence suggests that the extensive employment of adolescents increases their offending. We bring together insights garnered from life-course criminology, which emphasizes the timing of transitional role changes; and economic sociology, which draws attention to the "social embeddedness" of development and decision-making. The objective is to test whether a youth's embeddedness within the labor market has deleterious consequences for the youth's behavior. Our results show that work embeddedness is positively related to delinquency, and that this effect is not accounted for by prior levels of delinquent involvement. These findings were replicated by use of a community sample. In total our findings suggest that being embedded in a work role as a teenager has general deleterious consequences for behavior.